Shape Optimization of Multi-Chamber Tube-Extended Mufflers within Specified Back Pressures Using a Particle Swarm Method. (March 2013) - Chiu, Min-Chie
Recently, research on new techniques of single-chamber mufflers hybridized with an internal extended tube has been addressed; however, the research work on space-constrained multi-chamber mufflers conjugated with multiple internal extended tubes which may increase the acoustical performance within a specified back pressure has been neglected. Therefore, the main purpose of this paper is not only to analyze the sound transmission loss (STL) of a space-constrained tube-extended muffler equipped with 1∼3 chambers but also optimize the best design shape under a specified pressure drop. In this paper, the four-pole system matrix for evaluating acoustic performance – sound transmission loss (STL) – is derived. Moreover, a particle swarm optimization (PSO), a robust scheme used to search for the global optimum by imitating bird flocking or fish schooling behavior to achieve a self-evolving system, has been used during the optimization process. Before dealing with a broadband noise, the STL's maximization with respect to a one-tone noise is introduced for a reliability check on the PSO method. Additionally, an accuracy check of the mathematical model is performed. To appreciate the acoustical ability of the internal extended tubes and chambers inside a muffler, three kinds of multi-chamber mufflers hybridized with extended tubes (one-chamber, two-chamber, and three-chamber mufflers) have been assessed and compared. Results reveal that the maximal STL is precisely located at the desired tone. Consequently, a successful approach used for the optimal design of the tube-extended mufflers equipped with 1∼3 chambers under space and back pressure constrained conditions has been demonstrated.